Nursing as concrete philosophy, Part I: Risjord on nursing knowledge - Theodoridis, Kyriakos (Nursing philosophy, 2018)
This essay addresses the problem of the essentiality of nursing knowledge and what kind of theory, if any, is essential to nursing practice. The overarching aim of the essay was to argue for the thesis that nursing may be described as a kind of philosophical activity, and, consequently, that philosophy is the kind of "theory" that is essential to nursing practice and to the nursing discipline at large. The essay consists of two papers. The present paper, Part I, is a critical examination of Mark Risjord's discussion of the problem of the theory-practice gap in his Nursing Knowledge: Practice, Science, Philosophy, from 2010. According to Risjord, the cause of the theory-practice gap originates in an erroneous conception of science (logical positivism) which had a decisive influence upon the way nursing scholars appropriated theoretical frameworks for the nursing discipline. This philosophical influence is considered in effect to have generated the theory-practice gap. In order to bridge the gap, Risjord suggests, the nursing discipline needs to adopt a standpoint epistemology conjoined with a postpositivist conception of scientific theory. In this way, a legitimate brand of nursing science may be developed and the theory-practice gap overcome. I will argue that neither Risjord's diagnosis of the problem, nor his recommended cure, may succeed in rescuing the nursing discipline from the theory-practice gap. Rather, the real cause of the theory-practice gap, I will claim, derives from an erroneous conception of nursing (not of science), namely the conception of nursing as a kind of science (roughly speaking). On my view, to overcome the gap, the nursing discipline needs to make salient the inherently philosophical character of nursing. In the second paper (Part II), I will continue the discussion of nursing knowledge and delineate the thesis of nursing as a kind of concrete philosophy.